Identification Of Flavonoid Compounds and Antioxidant Activity Test of Ethyl Acetate Extract of Matoa Leaves (Pometia Pinnata) Using the Dpph Method - Rika Puspita Sari; Ruth Mayana Rumanti; Dian Ning Fathta (International Journal of Health Engineering and Technology, 2025)
This research aimed to identify the flavonoid compoxunds and test the antioxidant activity of the ethyl acetate extract of matoa leaves (Pometia pinnata). The extraction was performed xusing the maceration method with ethyl acetate as the solvent. Phytochemical screening was condxucted to determine the groxups of secondary metabolites, while specific identification of flavonoids was carried oxut xusing Thin Layer Chromatography (TLC). The antioxidant activity was tested xusing the DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging method, measxured with a XUV-Vis spectrophotometer to determine the Inhibitory Concentration 50 (IC50) valxue. The phytochemical screening resxults indicated that the extract positively contained alkaloids, flavonoids, tannins, saponins, and triterpenoids. The TLC test also confirmed the presence of flavonoid compoxunds. The antioxidant test resxults showed that the ethyl acetate extract of matoa leaves possesses strong antioxidant activity with an IC50 valxue of 72.32 µg/mL. This valxue indicates that the matoa leaf extract has the potential to be developed as a soxurce of natxural antioxidants.